Answer:
A^-1:B^-1
Step-by-step explanation:
im not 100% sure but i think this is the right answer :)
Answer:
A: Step 1: 6x − 10 = 1; Step 2: 6x = 11
Step-by-step explanation:
First: remove parentheses by multiplying factors.
6x - 10 = 1
Second: Move the constants to the right side of the equation
6x = 1 + 10
6x = 11
Answer:
This is quite simple when you consider it. go to -4 on the x axis and find where it goes on the y which in this case is 1. so the output for y is 1
Step-by-step explanation:
Answer:
n + y
Step-by-step explanation:
a² - b² = (a +b)(a - b)
÷
{ (n + y) in the denominator and numerator will be cancelled ;
(n - y) in the denominator and numerator will be cancelled
= n + y
It will be equivalent to (5y+9)
hope i was able to help and i wasn’t to late.